Gambaran Darah Kukang Dipelihara pada Kandang Penangkaran - Wirdateti Wirdateti; Ni Luh Putu Rischa Padmacanthy; Raden Taufiq Purna Nugraha; Gono Semiadi (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Maintenance of wildlife outside its original habitat is usually for the purposes of the exhibition in zoos, for research and captive breeding effort, especially for endangered species which eventually return to nature. The adaptability of the animals outside their original habitat can be seen from their health and their ability to reproduce in ex situ (captive) environment. One of the parameter that can be used to determine a health an animal is by observing their blood parameters and compared it with normal reference, however for many wild animals reference data for normal blood parameters are limited or not available. This study was conducted to determine a normal reference of blood parameters of slow lories that are kept in captive breeding condition, consisted of routine hematology and blood chemistry. This study used five animals consisting of four of N. coucang (1 male and three female) and one female N. javanicus. The results of the analysis showed that the value of hemoglobin, MCV, PDW, MPC, and erythrocytes (RBC) were higher on the male slow lories, while leukocytes (WBC), hematocrit, and MCHC were higher on the female. There were no significant differences between blood parameters of N. coucang and N. javanicus.